Effective Recovery of Gold from Chloride Multi-Metal Solutions Through Anion Exchange - Isabel F. F. Neto; Márcia A. D. Silva; Helena M. V. M. Soares (Recycling)
Leachates from electronic waste, slag dusts generated during the processing of electronic waste, sweeping jewelry, and municipal solid-waste incineration residues contain a myriad of base metals, such as aluminum (Al: 10–2000 mg/L), copper (Cu: 10–1000 mg/L), iron (Fe: 10–500 mg/L), nickel (Ni: 0.1–500 mg/L), lead (Pb: 1–500 mg/L), tin (Sn: 1–100 mg/L), and zinc (Zn: 5–500 mg/L), which are present at much higher quantities than Au (0.01–10 mg/L), which raises several drawbacks to the efficient recycling of Au with high purity using hydrometallurgical strategies. The aim of this work was to study the efficiency and selectivity of two strong basic anion exchange (DOWTM XZ-91419.00 and PurogoldTM A194) resins to recover Au from a chloride multi-metal solution containing these metals. For both resins, the adsorption kinetic and equilibrium parameters for Au(III), determined at 1.12 mol/L HCl, Eh = 1.1 V, and 25 °C, proceeded according to a pseudo-second order and a Langmuir isotherm (qmax was 0.94 and 1.70 mmol/g for DOWTM XZ-91419.00 and PurogoldTM A194 resins, respectively), respectively. Continuous adsorption experiments of Au (48 µmol/L; 2.0%) from a chloride multi-metal solution evidenced high Au retention capacity and selectivity to Au over Al, Cu, Fe, Ni, and Zn but low selectivity to Au over Ag and Sn for both resins. Concentrated (>3.3 mmol/L) and pure (>94%) Au eluates were obtained for both resins.